Traditional socio-cultural utilization and harvesting practices of an alpine medicinal herb, Neopicrorhiza scrophulariiflora in Khumbu Valley, Nepal - Ghimire, Narayan Prasad; Poudeyal, Mukti Ram; Gurung, Arati; Poudel , Mukti Ram; Bhattarai, Hari Datta; Ghimire, Suresh Kumar (Ethnobotany Research and Applications, 2023)
Background: This study aimed to document the traditional knowledge of people in the Khumbu Valley within Sagarmatha National Park and Buffer Zone in Nepal regarding the utilization and harvesting practices of the Himalayan medicinal plant Neopicrorhiza scrophulariiflora, which is under threat due to over-harvesting. Methods: The study used focus group discussions and key informant interviews to gather ethnobotanical knowledge from residents of seven enclave settlements of the park buffer zone. These settlements were later grouped into three village clusters based on their elevation. A total of 145 individuals of four ethnic groups with age between 20 and 72 years were interviewed. We analyzed the variation in the knowledge and usage of the plant among respondents in different village clusters, by gender, age-class, and ethnicity. Results: The majority of respondents were familiar with the plant and its medicinal value, mainly in the treatment of upper respiratory tract illnesses, gastrointestinal disorders, diabetes, and hypertension. There was no significant association between village clusters and the awareness of the plant’s use for specific diseases. However, there was a significant relationship between the village cluster and the number of use reports for different diseases. This suggests variations in the applications of the plant for treating specific ailments across different geographic locations. Females showed higher awareness of the plant’s medicinal uses, but gender did not significantly affect use reports for specific diseases or the overall number of use reports. Adults and seniors had the highest awareness of the plant’s medicinal uses, with use reports increasing with age class. Ethnicity did not significantly influence awareness or use reports. Rhizomes of N. scrophulariiflora are primarily collected for local use, sometimes exchanged among villagers or used as gifts. Preferred harvesting seasons varied by age, with older individuals favoring mature stages. Younger harvesters showed less concern for sustainable harvesting practices. Conclusions: N. scrophulariiflora is recognized for its potential in treating various health issues. The study reveals variations in the knowledge and utilization of N. scrophulariiflora based on geographic location, gender, and age-class, but not ethnicity. The study highlights a generational gap in the knowledge of plant usage, with younger generations losing traditional knowledge due to economic transformation, particularly as they transition to tourism-related livelihoods. To preserve this vital resource and its associated traditional knowledge, efforts should be made to educate and engage younger generations and promote sustainable harvesting practices in the region. Keywords: Kutki, Khumbu Valley, Destructive harvesting, Ethnobotanical uses